2016
DOI: 10.1042/bcj20160482
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of XBP1 in cancer signalling is regulated by PIN1

Abstract: XBP1 (X-box-binding protein 1) is activated in cancer and has a pivotal role in tumorigenesis and progression of human cancer. In particular, the XBP1 transcriptional regulatory network is well known to drive cancer development, but little is known about whether the stability of XBP1 is regulated and, if so, what controls the stability of XBP1. In the present study we show that PIN1 prolyl isomerase interacts with the active form of XBP1 (XBP1s) in a phosphorylation-dependent manner and promotes XBP1s-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Pin1 also stabilizes bromodomain-containing protein 4 (BRD4), a transactivator of multiple oncogenes, to promote the proliferation, migration, and invasion of gastric cancer 62 . Besides, Pin1 upregulates many other proliferation-inducing factors, including β-catenin 63 , FoxM1 64 , XBP1 65 , NUR77 66 , c-Jun 67 , and c-Myc 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Pin1 also stabilizes bromodomain-containing protein 4 (BRD4), a transactivator of multiple oncogenes, to promote the proliferation, migration, and invasion of gastric cancer 62 . Besides, Pin1 upregulates many other proliferation-inducing factors, including β-catenin 63 , FoxM1 64 , XBP1 65 , NUR77 66 , c-Jun 67 , and c-Myc 68 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no single mechanism that can fully explain the pathogenesis of tumor cell hyper-proliferation in HCC. Recent studies revealed that XBP1 was closely linked with tumor occurrence ( 4 , 8 , 10 12 ). Numerous researches have reported that the IRE1/XBP1 pathway is involved in cell survival, epithelial-mesenchymal transition, transcription factor regulation, drug resistance and glycolysis in tumor cells ( 8 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, p53 and AP4 act as transcriptional repressors and reduce the Pin1 transcription (Mitchell and Smith, 1988;Jeong et al, 2014). Xbp1 induces the transcription of p53 via HEPN1 and represses E2F1 via NF-κB activation, resulting in reduced Pin1 transcription (Chae et al, 2016). The transcription of PIN1 is repressed by BRCA1, a tumor suppressor gene (MacLachlan et al, 2000).…”
Section: Transcriptional and Post-translational Regulation Of Pin1 Inmentioning
confidence: 99%
“…PIN1 stabilizes BRD4 protein to increase the migration and proliferation of gastric cancer (Hu et al, 2017). It also upregulates c-Jun, c-Myc, FoxM1, β-catenin, NUR77, and XBP1 (Chen et al, 2012;Helander et al, 2015;Chae et al, 2016;Kruiswijk et al, 2016;Zhu et al, 2016;Csizmok et al, 2018).…”
Section: Transcriptional and Post-translational Regulation Of Pin1 Inmentioning
confidence: 99%